2014
DOI: 10.1177/0284185113515865
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of pleomorphic adenoma and Warthin’s tumor of the parotid gland: ultrasonographic features

Abstract: Ultrasound imaging characteristics, including multiple occurrences, shape, intrinsic cystic change, and the grade and distribution of tumor vessels, can be used to differentiate pleomorphic adenomas from Warthin's tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
4
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 31 publications
1
44
4
6
Order By: Relevance
“…We found no grayscale sonographic features of the tumors that were significantly different between the groups. The border characteristics of the tumors were not useful in distinguishing between the tumors in several earlier studies . In our study, most tumors showed well‐defined borders, and only 3 patients showed partially poorly defined borders.…”
Section: Discussioncontrasting
confidence: 89%
See 4 more Smart Citations
“…We found no grayscale sonographic features of the tumors that were significantly different between the groups. The border characteristics of the tumors were not useful in distinguishing between the tumors in several earlier studies . In our study, most tumors showed well‐defined borders, and only 3 patients showed partially poorly defined borders.…”
Section: Discussioncontrasting
confidence: 89%
“…Sonography is an effective method for detecting and localizing salivary gland tumors. However, even differentiating between the two most common salivary gland tumors, pleomorphic adenomas and Warthin tumors, is challenging on sonography …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations